2023
DOI: 10.1186/s13578-023-00995-8
|View full text |Cite
|
Sign up to set email alerts
|

The versatile roles of testrapanins in cancer from intracellular signaling to cell–cell communication: cell membrane proteins without ligands

Abstract: The tetraspanins (TSPANs) are a family of four-transmembrane proteins with 33 members in mammals. They are variably expressed on the cell surface, various intracellular organelles and vesicles in nearly all cell types. Different from the majority of cell membrane proteins, TSPANs do not have natural ligands. TSPANs typically organize laterally with other membrane proteins to form tetraspanin-enriched microdomains (TEMs) to influence cell adhesion, migration, invasion, survival and induce downstream signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…It has been reported that tetraspanins, including CD63, promote proliferation, migration and chemoresistance via activating PI3K/AKT signaling [ 82 ], and that TIMP-1 mediates apoptosis by activating cell survival signaling pathways involving PI3K/AKT [ 28 ]. Interestingly, we found that TIMP-1 silencing in chemoresistant Cis-Pt-R and Dox-R cells inhibits AKT phosphorylation, and that LY294002, a specific inhibitor of the PI3K/AKT pathway, makes soluble TIMP-1 unable to induce chemoresistance in MDA-MB-231 parental cells, thus suggesting that TIMP-1 could mediate chemoresistance by promoting this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tetraspanins, including CD63, promote proliferation, migration and chemoresistance via activating PI3K/AKT signaling [ 82 ], and that TIMP-1 mediates apoptosis by activating cell survival signaling pathways involving PI3K/AKT [ 28 ]. Interestingly, we found that TIMP-1 silencing in chemoresistant Cis-Pt-R and Dox-R cells inhibits AKT phosphorylation, and that LY294002, a specific inhibitor of the PI3K/AKT pathway, makes soluble TIMP-1 unable to induce chemoresistance in MDA-MB-231 parental cells, thus suggesting that TIMP-1 could mediate chemoresistance by promoting this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TSPAN is another the most powerful promoter of migrasome formation, enriched at the top of migrasomes and retraction fibers [ 27 ]. The concentration of TSPANs in migrasome membrane increases with time [ 28 ].…”
Section: Biogenesis and Removal Of Migrasomementioning
confidence: 99%
“…Studies have demonstrated the widespread expression of Tspans across various tissues and cell types, with many cells expressing multiple Tspan members [ 2 ]. The Tspan protein family in humans consists of 33 members, ranging from Tspan1 to Tspan33, with specific tissue-specific expression patterns [ 3 ]. For instance, Tspan5 exhibits high expression in cortical regions and Purkinje cells [ 4 ], while Tspan7 is highly expressed in brain tissue and islets [ 5 , 6 ], Moreover, Tspan26 represents a B-cell-surface antigen that demonstrates widespread expression in mature B cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%